2021
DOI: 10.3390/foods10112777
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive and Selective Fluorescent Probe Using MPA-InP/ZnS QDs for Detection of Trace Amounts of Cu2+ in Water

Abstract: Detection of copper (II) ions (Cu2+) in water is important for preventing them from entering the human body to preserve human health. Here, a highly sensitive and selective fluorescence probe that uses mercaptopropionic acid (MPA)-capped InP/ZnS quantum dots (MPA-InP/ZnS QDs) was proposed for the detection of trace amounts of Cu2+ in water. The fluorescence of MPA-InP/ZnS QDs can be quenched significantly in the presence of Cu2+, and the fluorescence intensity shows excellent linearity when the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Diffusive encounters and collision contact can be attributed to the dynamic quenching process, while new complex forms without changes in fluorescence lifetime will be assigned to the static quenching process [52]. However, dynamic quenching (i.e., FRET, PET) can cause changes in the fluorescence lifetime of fluorescence QDs after adding analytes, while these changes cannot be observed in IFEs and SQEs [53]. In addition, the fluorescence enhancement of QDs caused by the interaction of QDs and analytes can be attributed to surface plasmon enhanced fluorescence (SPEF), which is also referred to as metal surface enhanced fluorescence (MEF) and chelate enhanced fluorescence (CHEF).…”
Section: Mechanisms Of Fluorescence Sensorsmentioning
confidence: 99%
“…Diffusive encounters and collision contact can be attributed to the dynamic quenching process, while new complex forms without changes in fluorescence lifetime will be assigned to the static quenching process [52]. However, dynamic quenching (i.e., FRET, PET) can cause changes in the fluorescence lifetime of fluorescence QDs after adding analytes, while these changes cannot be observed in IFEs and SQEs [53]. In addition, the fluorescence enhancement of QDs caused by the interaction of QDs and analytes can be attributed to surface plasmon enhanced fluorescence (SPEF), which is also referred to as metal surface enhanced fluorescence (MEF) and chelate enhanced fluorescence (CHEF).…”
Section: Mechanisms Of Fluorescence Sensorsmentioning
confidence: 99%
“…E-mail: 202161105067@njtech.edu.cn, 939282366@qq.com, 202261205195@njtech.edu.cn, yaocheng@njtech.edu.cn applications. 17,18 CdTe QDs have been reported to be of great advantage in the detection of antibiotic drugs. [19][20][21] At the same time, Y 3+ enhances the single-signal emission of tetracycline, and Y 3+ has been successfully used for sensing the detection of tetracycline.…”
Section: 1039/d3an00921amentioning
confidence: 99%
“…Quantum dots (QDs), being highly environmentally stable, photo-stable, and brightly fluorescent materials, have unique size and composition-tunable fluorescence characteristics, 16 which make them very attractive for fluorescence sensing applications. 17,18 CdTe QDs have been reported to be of great advantage in the detection of antibiotic drugs. 19–21 At the same time, Y 3+ enhances the single-signal emission of tetracycline, and Y 3+ has been successfully used for sensing the detection of tetracycline.…”
Section: Introductionmentioning
confidence: 99%
“…The ic-ELISA method based on the nanobody N56 was validated with spiked water sample and confirmed by UPLC-MS/MS, which indicated that the ic-ELISA established in this work is a reproducible detection assay for nodularin residues in water samples. Xu et al [12] prepared a highly sensitive and selective fluorescence probe that used mercaptopropionic acid (MPA)-capped InP/ZnS quantum dots (MPA-InP/ZnS QDs) for the detection of trace amounts of Cu 2+ in water. This probe exhibited an extremely low limit of detection of 0.22 nM.…”
mentioning
confidence: 99%